Legal Basis for Conventional and Sharia Investments in the Indonesian Capital Market - Witro, Doli (Journal of Economicate Studies, 2021)
This article examines the legal basis for a conventional investment as well as sharia investment in the Indonesian capital market. This study focuses on the history of the formation and legal basis of investment in the capital market and is then continued by classifying conventional investment regulations and Islamic investment in Indonesia. This study aims to explain the history of the formation, basis, and legal basis for sharia and conventional investment in the Indonesian capital market. This research is a qualitative study using a normative jurisdiction approach. This article is a document study and library research. The data analysis techniques used were data reduction, data presentation, and conclusion drawing. The analysis results show that investment can be interpreted as the investment of money or capital in a company or project that aims to make a profit. The Indonesian capital market system, activities in the conventional investment capital market, and sharia investment initially referred to Law Number 8 of 1995 concerning the Capital Market, which technical regulations for its implementation are regulated in Bapepam-LK (Financial Services Authority) Regulations, Government Regulations, Stock Exchange Regulations and others.